EFFECT OF AZOLLA AS SOURCE OF NITROGEN ON THE GROWTH AND YIELD OF PECHAY (Brassica napus L. var. chinensis) - Cuevas, Zenaida M.; Santiago, Rebecco M.; Briones, Elizabeth D. (Annals of Tropical Research, 1988)
Plants applied with either azolla or inorganic fertilizer performed better than the unfertilized ones. Increasing the rate of azolla application from 120 to 210 kg N/ha correspondingly increased all the parameters measured and the net income during the first cropping. However in the second cropping, all the para-meters considered and the net income tremendously decreased. Highest yield and net return in both croppings were obtained from application of 210 kg N/ha from azolla while the unfertilized control showed the lowest values. Application of the same amounts of nitrogen (165 kg N/ha) from azolla (T3) and inorganic fertilizer (T₁) did not produce significant differences in all parameters during the first cropping. However during the second cropping, T3 but not T₁ produced higher average weight per plant and yield than the control. The soil pH and organic matter, phosphorus and potassium contents in-creased as the rate of azolla application was raised from 120 kg to 210 kg N/ha.